Educational Product: endorsement of a site as a platform for environmental education, dissemination and social articulation (Research, Society and Development, 2024)
This article is the second part of the evaluation carried out by teaching specialization students on the website developed as an Educational Product (PE) of the professional doctorate in science teaching at the Federal Institute of Education, Science and Technology of Rio de Janeiro (IFRJ) in 2024, comprising part of the book: Pedagogical Practices - Innovative Approaches and Methodologies, by the publisher Inovar. This excerpt is a complement not presented in the book. Since, the first part was dedicated to the analysis of the quantitative data of the thesis and, for the present article, we will pay attention to the qualitative data, with the objective of presenting results of the discursive evaluation, of the first evaluators of the website as an Educational Product. As a methodology, we used a brief description of the discursive data, where we have the narratives of these evaluators, in their perceptions about the website, data resulting from the questionnaire created in Google Forms and applied as a non-scored task, in the discipline in Management in Technical Professional Education (Management in EPT) in the specialization course in Teaching for Professional Technological Education - DocEPT. The theoretical references that support us are Hernández and Ventura; Saviani; Zanotto and Rose; Guimarães; Freire and Morin; Almeida and Grubisich; Anjos, Rôças; Pereira, authors in the teaching area; curriculum and projects, directing us towards analysis and discussion.